Night school [videorecording (DVD)] (Oscilloscope Laboratories, 2017)
Indianapolis has one of the lowest high school graduation rates in the country. For adult learners, Greg, Melissa, and Shynika, finally earning their high school diplomas could be a life-changing achievement. Andrew Cohn's absorbing documentary observes their individual pursuits, and the broader systemic roadblocks faced by many low income Americans. -- Adapted from container.